1989
DOI: 10.1002/eji.1830190932
|View full text |Cite
|
Sign up to set email alerts
|

Restricted usage of VH and VX genes by murine monoclonal antibodies against 3‐fucosyllactosamine

Abstract: We are studying the structure and regulation of murine antibodies against the 3-fucosyllactosamine antigenic determinant. Analysis of the sequences of seven BALB/c IgM, kappa monoclonal antibodies (mAb), obtained from four fusions, indicates that these antibodies exhibit restriction in their usage of VH and VL genes. Based on a combination of mRNA sequences and Southern filter hybridization data, all seven light chains are encoded by V kappa 24B and J kappa 1 gene segments. Complete mRNA sequences of the heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
(8 reference statements)
0
25
0
Order By: Relevance
“…We exploited the alanine scan strategy to identify functionally important residues of the Fv. It is very likely that V H CDR3 region is the primary antigen binding site of HA22 Fv because V H CDR3 is the primary antigen binding site in most antibodies, 17,18 and because our previous studies using a phage-based in vitro evolution method 10,13 showed that Thr 100 -His 100a -Trp 100b in V H CDR3 is the only region whose modification drastically altered the affinity of HA22 Fv. Also, insertion of Gly before and after this region greatly reduced the activity of HA22 immunotoxin (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…We exploited the alanine scan strategy to identify functionally important residues of the Fv. It is very likely that V H CDR3 region is the primary antigen binding site of HA22 Fv because V H CDR3 is the primary antigen binding site in most antibodies, 17,18 and because our previous studies using a phage-based in vitro evolution method 10,13 showed that Thr 100 -His 100a -Trp 100b in V H CDR3 is the only region whose modification drastically altered the affinity of HA22 Fv. Also, insertion of Gly before and after this region greatly reduced the activity of HA22 immunotoxin (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the highly evolved nature of the germ-line response to carbohydrate antigens and of the potential relationship between the V, D, and J gene segments is provided by the phenomenon of "V region restriction," where a given antigen will evoke a population of antibodies constructed from a small number of V genes combined with a number of different D and J genes (10,(12)(13)(14).…”
mentioning
confidence: 99%
“…It is interesting that V~4 4 1 is used to encode antibodies against a number of carbohydrate antigens, and we suggested previously [4] that the structure encoded by this VH gene segment may possess structural features that makes it particularly well adapted for anti-carbohydrate binding sites. The V~441-encoded anti-carbohydrate antibodies provide an interesting system for studying structurefunction relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Total cellular RNA was prepared by the method of Chomczynski and Sacchi [12]. Sequencing was performed by a minor modification of the method of Geliebter et al [13], as previously described [4]. Additional sequence data were obtained by dideoxynucleotide sequencing [ 141 of single and doublestranded DNA templates, using Sequenase (US Biochemicals, Cleveland, OH) according to the manufacturer's instructions.…”
Section: Sequencingmentioning
confidence: 99%
See 1 more Smart Citation